The triple work-up for emergency department patients with acute chest pain: how often does it occur? - Rogg, Jonathan G.; De Neve, Jan-Walter; Huang, Calvin; Brown, David; Jang, Ik-Kyung; Chang, Yuchiao; Marill, Keith; Parry, Blair; Hoffmann, Udo; Nagurney, John T. (The journal of emergency medicine, 2008)
Objectives: To measure the degree of overlap and diagnostic yield for evaluations of acute coronary syndrome (ACS), pulmonary embolism (PE), and aortic dissection (AD) among Emergency Department (ED) patients. Methods: We conducted a cross-sectional descriptive study of consecutive adult patients seen in the ED of a 78,000-annual-visit urban academic medical center. Patients who had received at least one of eight of the tests used in our ED to diagnose these three diseases were identified through three methods, and a final study population list was created. Overlap of evaluations and diagnostic yields were calculated by simple descriptive statistics. Results: Over a 2-week period, 626 patient encounters among 622 unique patients were identified. Among these 626 visits, 139 (22%) included diagnostic tests for more than one of the three diagnoses of interest. The majority of these multiple tests were for ACS plus PE (n = 121, 87% of all multiple tests), whereas a minority of patients received tests for ACS plus AD (n = 14, 10% of all multiple tests) or for the “triple work-up” of ACS plus PE plus AD (n = 4, 2.9% of all multiple tests). Conclusion: Although the “triple work-up” evaluation for ACS, PE, and AD is relatively uncommon, a significant number of ED patients who are evaluated for at least one of these three major chest pain syndromes receive simultaneous testing for one of the others.
Available online 14 September 2008
Gesehen am 17.12.2020